Visual and Chemical Prey Cues as Complementary Predator Attractants in a Tropical Stream Fish Assemblage - Chris K. Elvidge; Grant E. Brown (International Journal of Zoology)
To date, little attention has been devoted to possible complementary effects of multiple forms of public information similar information on the foraging behaviour of predators. In order to examine how predators may incorporate multiple information sources, we conducted a series of predator attraction trials in the Lower Aripo River, Trinidad. Four combinations of visual (present or absent) and chemical cues (present or absent) from each of two prey species were presented. The occurrences of three locally abundant predatory species present within a 1 m radius of cue introduction sites were recorded. The relative attractiveness of cue type to each predator was directly related to their primary foraging modes, with visual ambush predators demonstrating an attraction to visual cues, benthivores to chemical cues, and active social foragers demonstrating complementary responses to paired cues. Predator species-pair counts were greatest in response to cues from the more abundant prey species, indicating that individuals may adopt riskier foraging strategies when presented with more familiar prey cues. These differences in predator attraction patterns demonstrate complementary effects of multiple sensory cues on the short-term habitat use and foraging behaviour of predators under fully natural conditions.